Fiqh Muamalah Analysis of The Wage System in Ijarah Contract for Content Creator in Medan City - Dias Putra Prayogi; Zuhirsyan, Muhammad; Agus, Rizal (Business Finance Analyst Co., 2025)
This study aims to analyze the wage system in the Ijarah contract for content creators in Medan City from the perspective of fiqhmuamalah. The background of this research is based on the growing prominence of the content creator profession in the digital era, particularly on social media platforms such as Instagram and TikTok, as well as the limited understanding of contractual agreements in accordance with sharia principles. This research employs a qualitative approach with data collection techniques through in-depth interviews involving content creators, the Indonesian Ulema Council (MUI) of Medan, and Islamic economics experts. The findings indicate that wage practices still show several inconsistencies with the principles of the Ijarah contract, such as a lack of clarity in work agreements, delayed payments, and vague wage amounts. Moreover, content creators’ understanding of fiqhmuamalah, particularly the Ijarah contract, remains limited. Therefore, education and guidance are necessary to ensure that collaborations between content creators and business actors can proceed professionally, fairly, and in accordance with Islamic law.